Preparation method of amorphous lithium ion battery negative electrode material
By mixing and calcining the tin source, phytol hexaphosphate and carbon source in an inert atmosphere, amorphous lithium-ion battery negative electrode material was prepared, which solved the problem of volume expansion and structural collapse of the tin pyrophosphate material during charging and discharging, and achieved electrochemical performance with high capacity and good cycle stability.
Patent Information
- Application Number
- CN202411798423.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
AI Technical Summary
The existing lithium-ion battery negative electrode material tin pyrophosphate has problems such as volume expansion, increase resistance and structural collapse during charging and discharging, resulting in poor circulation performance.
Amorphous lithium-ion battery negative electrode material was prepared by mixing the tin source, phytol hexaphosphate and carbon source in an inert atmosphere, and calcining it under an inert atmosphere.
The prepared amorphous tin pyrophosphate material has ultra-high capacity and good cycle stability, which can maintain structural stability under high current density and significantly improve electrochemical performance.
Smart Images

Figure CN119612465A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing an amorphous lithium ion battery negative electrode material. Background Art
[0002] Tin-based materials have the advantages of high theoretical specific capacity, environmental friendliness and low working potential. However, there is a large volume change in the subsequent lithium ion deintercalation process, and the internal stress caused can easily lead to electrode pulverization and a serious decrease in capacity. In addition, the tin particles generated by the reaction will agglomerate into tin clusters, further reducing the electrochemical activity. Tin pyrophosphate is a polyanion compound. This polyanion skeleton is easy to synthesize, has a strong structure and good alkaline ion mobility. However, the theoretical specific capacity of tin pyrophosphate itself is not high (769.8mAh g -1 ), the conductivity is low, and a large volume change will occur during the charge and discharge cycle, which increases the resistance and collapses the structure, resulting in poor cycle performance.
[0003] At present, the existing technology suppresses the volume expansion of tin pyrophosphate materials by preparing a variety of structures. For example, the spray drying method is used to synthesize mesoporous spherical structures. Capillary waves combine the particles on the gas droplets produced during the atomization process, and form a spherical structure during the decomposition of these gases, thereby forming a cavity inside the sphere and forming hollow microspheres with high tap density. On the one hand, the above method has high requirements for experimental equipment, complex operation, and low yield; on the other hand, the structure formed is still prone to structural collapse under high current density, resulting in poor cycle performance of the material during application. Summary of the invention
[0004] Purpose of the invention: The purpose of the present invention is to provide a method for preparing an amorphous lithium-ion battery negative electrode material. The tin pyrophosphate prepared by the method is amorphous, and the amorphous tin pyrophosphate has ultra-high capacity and good cycle stability.
[0005] Technical solution: The method for preparing the amorphous lithium-ion battery negative electrode material of the present invention comprises the following steps:
[0006] (1) mixing a tin source, phytic acid and a carbon source in an inert atmosphere, and stirring them thoroughly to obtain a mixed solution. The purpose of mixing in an inert atmosphere is to prevent the possibility of the raw materials reacting with air and to reduce the degree of hydrolysis;
[0007] (2) freeze-drying the obtained mixed solution to obtain a precursor material;
[0008] (3) calcining the precursor material under an inert atmosphere to obtain an amorphous lithium-ion battery negative electrode material.
[0009] Wherein, in step (1), the tin source is at least one of tin tetrachloride pentahydrate, stannous chloride, tin sulfate or sodium stannate.
[0010] Wherein, in step (1), the carbon source is at least one of citric acid monohydrate, oxalic acid or ascorbic acid.
[0011] Wherein, in step (1), the phytic acid is a phytic acid solution with a volume fraction of 70 to 75%.
[0012] Wherein, in step (1), the molar ratio of the tin source, phytic acid and carbon source added is 1:3-4:1-2.
[0013] Wherein, in step (1), the stirring time is 0.5 to 2 hours, and the solution is stirred to such an extent that the volume of the solution is reduced to 50% of the initial volume, which can reduce the time required for freeze drying while avoiding crystal precipitation.
[0014] Among them, in step (2), the corresponding parameters for freeze-drying are storage at -35 to -30°C in a vacuum environment for 8 to 10 hours.
[0015] Wherein, in step (3), the heating rate of calcination is 5-10°C / min, the calcination temperature is 400-600°C, the calcination time is 3-5h, and the cooling rate is 3-5°C / min.
[0016] Wherein, in step (3), the inert atmosphere is nitrogen or argon.
[0017] Wherein, in step (3), the amorphous lithium-ion battery negative electrode material is amorphous SnP2O7.
[0018] The isotropic amorphous structure can provide abundant diffusion pathways for alkali ions and can also adapt well to the volume expansion during the charge and discharge process. At the same time, amorphous tin pyrophosphate has a longer Sn-O bond than crystalline materials, so that the intercalation reaction takes precedence over the conversion reaction, which is beneficial to increase the Li + storage, so this amorphous tin pyrophosphate exhibits very excellent electrochemical properties.
[0019] The amorphous lithium-ion battery negative electrode material prepared by the present invention is assembled into a CR2025 button battery. After charge and discharge tests, the negative electrode material can be used for 500 mA g at a voltage of 0.01 to 3 V. -1 The first discharge capacity of the material can reach 1047 mAh g -1 ; at 500mAg -1 When the reversible discharge capacity is maintained at 1021.2 mAh g after 500 cycles to 900 cycles. -1 ; at 2000mA g -1 After 1400 cycles, the reversible discharge capacity remains at 600 mAh g -1 above.
[0020] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The method of the present invention is simple in process and has a high product yield; (2) The method of the present invention can prepare amorphous tin pyrophosphate. The amorphous structure can provide abundant ion diffusion pathways during application as a negative electrode material for lithium-ion batteries, thereby achieving rapid diffusion of internal lithium ions and adapting to the volume change of the negative electrode material during charge and discharge, thereby enhancing cycle stability, thereby effectively improving the electrochemical properties of the electrode material and enabling the battery to have ultra-high capacity and good cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is the XRD pattern of the sample in Example 5;
[0022] Figure 2 This is the SEM image of the sample obtained in Example 5;
[0023] Figure 3 TEM image of the sample obtained in Example 5;
[0024] Figure 4 The electrochemical CV diagram of the sample obtained in Example 5;
[0025] Figure 5 The battery assembled from the sample obtained in Example 5 was -1 Cycle curve diagram under multiple rates;
[0026] Figure 6 The battery assembled from the sample obtained in Example 5 was 1000 mAg -1 Cycle curve diagram under multiple rates. DETAILED DESCRIPTION
[0027] Example 1
[0028] The method for preparing the amorphous lithium-ion battery negative electrode material of the present invention comprises the following steps:
[0029] (1) In a dry fume hood, weigh 0.8 g of tin tetrachloride pentahydrate and add it to 4 mL of phytic acid solution (phytic acid aqueous solution, the volume fraction of phytic acid is 70%), and continue to stir at 25°C. Then weigh 0.4 g of citric acid monohydrate (C6H8O7·H2O) and slowly add it to the above solution. Continue to stir until the solution is reduced to 2 mL.
[0030] (2) Freeze the clear solution in advance and place it in a freeze drying oven at -30°C for 10 h in vacuum;
[0031] (3) The dried sample was placed in a tubular furnace and heated to 600°C at a rate of 5°C / min under an argon atmosphere for calcination for 3 h, and then cooled to room temperature at a rate of 3°C / min to obtain SnP2O7, a negative electrode material for lithium-ion batteries, with a product yield of 99.9%.
[0032] The amorphous SnP2O7 prepared in Example 1, the conductive agent Super-P and the binder carboxymethyl cellulose (CMC) were uniformly mixed in a mass ratio of 8:1:1 to obtain a mixture; according to the amount of the mixture, an appropriate amount of deionized water was added, and the mixture was ground into a gel state and then evenly coated on the current collector copper foil, placed in an 80°C vacuum drying oven for drying for 12 hours, and the electrode sheet was punched out with a punch, and then assembled into a button battery in an argon glove box in the order of positive electrode shell-lithium sheet-electrolyte-diaphragm-electrolyte-electrode sheet-gasket-spring sheet-negative electrode shell, and finally the button battery was sealed with a press. Among the components of the button battery, the diaphragm is a polypropylene film (Celgard2300) and the electrolyte is a 1 mol / L LiPF6 solution.
[0033] The button battery obtained above was subjected to constant current charge and discharge test. At a voltage of 0.01-3V, the -1 The first discharge capacity of the material can reach 1107 mAh g -1 After 900 cycles, the reversible discharge capacity remains at 945.2 mAh g -1 ; at 2000mA g -1 After 1400 cycles, the reversible discharge capacity remains at 510.1 mAh g -1 .
[0034] Example 2
[0035] The method for preparing the amorphous lithium-ion battery negative electrode material of the present invention comprises the following steps:
[0036] (1) In a dry fume hood, weigh 0.8 g of tin tetrachloride pentahydrate and add it to 4 mL of phytic acid solution (phytic acid aqueous solution, the volume fraction of phytic acid is 70%), and stir continuously at 25°C. Then weigh 0.6 g of citric acid monohydrate (C6H8O7·H2O) and slowly add it to the above solution. Continue stirring until the solution is reduced to 2 mL.
[0037] (2) Freeze the clear solution in advance and place it in a freeze drying oven at -30°C for 10 h in vacuum;
[0038] (3) The dried sample was placed in a tubular furnace and heated to 550°C at a rate of 5°C / min under an argon atmosphere and calcined for 3 h. The sample was then cooled to room temperature at a rate of 3°C / min to obtain SnP2O7, a negative electrode material for lithium-ion batteries, with a product yield of 99.9%.
[0039] The amorphous SnP2O7 prepared in Example 2, the conductive agent Super-P and the binder carboxymethyl cellulose (CMC) were uniformly mixed in a mass ratio of 8:1:1 to obtain a mixture; according to the amount of the mixture, an appropriate amount of deionized water was added, and the mixture was ground into a gel state and then evenly coated on the current collector copper foil, placed in an 80°C vacuum drying oven for drying for 12 hours, and the electrode sheet was punched out with a punch, and then assembled into a button battery in an argon glove box in the order of positive electrode shell-lithium sheet-electrolyte-diaphragm-electrolyte-electrode sheet-gasket-spring sheet-negative electrode shell, and finally the button battery was sealed with a press. Among the components of the button battery, the diaphragm is a polypropylene film (Celgard2300) and the electrolyte is a 1 mol / L LiPF6 solution.
[0040] The button battery obtained above was subjected to constant current charge and discharge test. At a voltage of 0.01-3V, the -1 When the material is discharged for the first time, the specific capacity can reach 1052.2 mAh g -1 After 900 cycles, the reversible discharge capacity remains at 942.7 mAh g -1 ; at 2000mAg -1 After 1400 cycles, the reversible discharge capacity remains at 549.5 mAh g -1 .
[0041] Example 3
[0042] The method for preparing the amorphous lithium-ion battery negative electrode material of the present invention comprises the following steps:
[0043] (1) In an Ar atmosphere glove box, weigh 0.8 g of tin tetrachloride pentahydrate and add it to 4 mL of phytic acid solution (phytic acid aqueous solution, the volume fraction of phytic acid is 70%), and continue stirring at 25°C. Then weigh 0.4 g of citric acid monohydrate (C6H8O7·H2O) and slowly add it to the above solution. Continue stirring until the solution is reduced to 2 mL and the water vapor content in the glove box is less than 0.1 ppm.
[0044] (2) Freeze the clear solution in advance and place it in a freeze drying oven at -30°C for 10 h in vacuum;
[0045] (3) The dried sample was placed in a tubular furnace and heated to 600°C at a rate of 5°C / min under an argon atmosphere for calcination for 3 h, and then cooled to room temperature at a rate of 3°C / min to obtain SnP2O7, a negative electrode material for lithium-ion batteries, with a product yield of 99.9%.
[0046] The amorphous SnP2O7 prepared in Example 3, the conductive agent Super-P and the binder carboxymethyl cellulose (CMC) were uniformly mixed in a mass ratio of 8:1:1 to obtain a mixture; according to the amount of the mixture, an appropriate amount of deionized water was added, and the mixture was ground into a gel state and then evenly coated on the current collector copper foil, placed in an 80°C vacuum drying oven for drying for 12 hours, and the electrode sheet was punched out with a punch, and then assembled into a button battery in an argon glove box in the order of positive electrode shell-lithium sheet-electrolyte-diaphragm-electrolyte-electrode sheet-gasket-spring sheet-negative electrode shell, and finally the button battery was sealed with a press. Among the components of the button battery, the diaphragm is a polypropylene film (Celgard2300) and the electrolyte is a 1 mol / L LiPF6 solution.
[0047] The button battery obtained above was subjected to constant current charge and discharge test. At a voltage of 0.01-3V, the -1 When the material is discharged for the first time, the specific capacity can reach 1018 mAh g -1 After 900 cycles, the reversible discharge capacity remains at 912.6 mAh g -1 ; at 2000mA g -1 After 1400 cycles, the reversible discharge capacity remains at 592.0 mAh g -1 .
[0048] Example 4
[0049] The method for preparing the amorphous lithium-ion battery negative electrode material of the present invention comprises the following steps:
[0050] (1) In an Ar atmosphere glove box, weigh 0.8 g of tin tetrachloride pentahydrate and add it to 5 mL of phytic acid solution (phytic acid aqueous solution, the volume fraction of phytic acid is 70%), and continue stirring at 25°C. Then weigh 0.4 g of citric acid monohydrate (C6H8O7·H2O) and slowly add it to the above solution. Continue stirring until the solution is reduced to 2.5 mL and the water vapor content in the glove box is less than 0.1 ppm;
[0051] (2) Freeze the clear solution in advance and place it in a freeze drying oven at -30°C for 10 h in vacuum;
[0052] (3) The dried sample was placed in a tubular furnace and heated to 400°C at a rate of 5°C / min under an argon atmosphere for calcination for 3.5 h, and then cooled to room temperature at a rate of 3°C / min to obtain SnP2O7, a negative electrode material for lithium-ion batteries, with a product yield of 99.9%.
[0053] The amorphous SnP2O7 prepared in Example 4, the conductive agent Super-P and the binder carboxymethyl cellulose (CMC) were uniformly mixed in a mass ratio of 8:1:1 to obtain a mixture; according to the amount of the mixture, an appropriate amount of deionized water was added, and the mixture was ground into a gel state and then evenly coated on the current collector copper foil, placed in an 80°C vacuum drying oven for drying for 12 hours, and the electrode sheet was punched out with a punch, and then assembled into a button battery in an argon glove box in the order of positive electrode shell-lithium sheet-electrolyte-diaphragm-electrolyte-electrode sheet-gasket-spring sheet-negative electrode shell, and finally the button battery was sealed with a press. Among the components of the button battery, the diaphragm is a polypropylene film (Celgard2300) and the electrolyte is a 1 mol / L LiPF6 solution.
[0054] The button battery obtained above was subjected to constant current charge and discharge test. At a voltage of 0.01-3 V, the battery was charged and discharged at 500 mA g -1 The first discharge capacity of the material can reach 1048.0 mAh g -1 After 900 cycles, the reversible discharge capacity remains at 899.2 mAh g -1 ; at 2000mA g -1 After 1400 cycles, the reversible discharge capacity remains at 507.3 mAh g -1 .
[0055] The button cell obtained above was subjected to constant current charge and discharge test. At a voltage of 0.01-3 V, the -1 The first discharge capacity of the material can reach 1248.0 mAh g -1 ; at 1000mA g -1 After 500 cycles, the reversible discharge capacity remains at 570.3 mAh g -1 .
[0056] Example 5
[0057] The method for preparing the amorphous lithium-ion battery negative electrode material of the present invention comprises the following steps:
[0058] (1) In an Ar atmosphere glove box, weigh 0.8 g of tin tetrachloride pentahydrate and add it to 5 mL of phytic acid solution (phytic acid aqueous solution, the volume fraction of phytic acid is 70%), and continue stirring at 25°C. Then weigh 0.6 g of citric acid monohydrate (C6H8O7·H2O) and slowly add it to the above solution. Continue stirring until the solution is reduced to 2.5 mL and the water vapor content in the glove box is less than 0.1 ppm;
[0059] (2) Freeze the clear solution in advance and place it in a freeze drying oven at -30°C for 10 h in vacuum;
[0060] (3) The dried sample was placed in a tubular furnace and heated to 500°C at a rate of 5°C / min under an argon atmosphere for calcination for 4 h, and then cooled to room temperature at a rate of 3°C / min to obtain SnP2O7, a negative electrode material for lithium-ion batteries, with a product yield of 99.9%.
[0061] The amorphous SnP2O7 prepared in Example 5, the conductive agent Super-P and the binder carboxymethyl cellulose (CMC) were uniformly mixed in a mass ratio of 8:1:1 to obtain a mixture; according to the amount of the mixture, an appropriate amount of deionized water was added, and the mixture was ground into a gel state and then evenly coated on the current collector copper foil, placed in an 80°C vacuum drying oven for drying for 12 hours, and the electrode sheet was punched out with a punch, and then assembled into a button battery in an argon glove box in the order of positive electrode shell-lithium sheet-electrolyte-diaphragm-electrolyte-electrode sheet-gasket-spring sheet-negative electrode shell, and finally the button battery was sealed with a press. Among the components of the button battery, the diaphragm is a polypropylene film (Celgard2300) and the electrolyte is a 1 mol / L LiPF6 solution.
[0062] The button battery obtained above was subjected to constant current charge and discharge test. At a voltage of 0.01-3V, the -1 The first discharge capacity of the material can reach 1047 mAh g -1 After 900 cycles, the reversible discharge capacity remains at 1021.2 mAh g -1 ,like Figure 5 As shown; at 2000mA g -1 After 1400 cycles, the reversible discharge capacity remains at 642.9 mAh g -1 ,like Figure 6 It can be concluded that the material of Example 5 can effectively inhibit or alleviate the volume expansion problem of SnP2O7, and improve the electronic and ion conductivity of the material itself, thereby improving the electrochemical performance and cycle stability of the material, and achieving ultra-high capacity and good cycle stability of the material.
[0063] like Figure 1 As shown, the SnP2O7 prepared in Example 5 has an amorphous structure. Most of the diffraction peaks of the Example 5 material shown in the figure are consistent with the standard XRD diffraction peaks of SnP2O7 (PDF#29-1352), indicating that amorphous SnP2O7 is prepared at a sintering temperature of 500°C. Under the conditions of Example 5, the sintering temperature is increased to 650°C, and SnP2O7 with a crystalline structure is obtained.
[0064] like Figure 2 As shown, the SnP2O7 material prepared in Example 5 is composed of block-shaped SnP2O7 with wrinkled surface and spherical SnP2O7 grown from and attached to the surface. Such a structure can increase the contact area between the material and the electrolyte, which is beneficial to the deintercalation of ions, so that the material exhibits excellent electrochemical properties; at the same time, the amorphous structure provides abundant ion diffusion pathways, and can adapt to the volume change of the negative electrode material during the charge and discharge process, providing higher structural stability.
[0065] like Figure 3 As shown in the TEM image of the sample obtained in Example 5, it can be seen that no sub-nanometer clusters, no lattice fringes, and no obvious agglomeration phenomenon are observed. In the corresponding SAED pattern, only unclear diffraction ring elements can be observed. The mapping image shows that the distribution ranges of O, P and Sn atoms are relatively overlapping, and C atoms are relatively evenly distributed around the above atoms. Figure 4 As shown in the electrochemical CV diagram of the sample obtained in Example 5, after the initial cycle, the reduction peak and the oxidation peak mostly overlap, proving that the material + Remarkable electrochemical reversibility during insertion and extraction.
[0066] Example 6
[0067] The method for preparing the amorphous lithium-ion battery negative electrode material of the present invention comprises the following steps:
[0068] (1) In an Ar atmosphere glove box, weigh 0.8 g of tin tetrachloride pentahydrate and add it to 6 mL of phytic acid solution (phytic acid aqueous solution, the volume fraction of phytic acid is 70%), and continue to stir at 25°C. Then weigh 0.6 g of citric acid monohydrate (C6H8O7·H2O) and slowly add it to the above solution. Continue to stir until the solution is reduced to 3 mL and the water vapor content in the glove box is less than 0.1 ppm.
[0069] (2) Freeze the clear solution in advance and place it in a freeze drying oven at -30°C for 10 h in vacuum;
[0070] (3) The dried sample was placed in a tubular furnace and heated to 500°C at a rate of 5°C / min under an argon atmosphere for calcination for 4 h, and then cooled to room temperature at a rate of 3°C / min to obtain SnP2O7, a negative electrode material for lithium-ion batteries, with a product yield of 99.9%.
[0071] The amorphous SnP2O7 prepared in Example 6, the conductive agent Super-P and the binder carboxymethyl cellulose (CMC) were uniformly mixed in a mass ratio of 8:1:1 to obtain a mixture; according to the amount of the mixture, an appropriate amount of deionized water was added, and the mixture was ground into a gel state and then evenly coated on the current collector copper foil, placed in an 80°C vacuum drying oven for drying for 12 hours, and the electrode sheet was punched out with a punch, and then assembled into a button battery in an argon glove box in the order of positive electrode shell-lithium sheet-electrolyte-diaphragm-electrolyte-electrode sheet-gasket-spring sheet-negative electrode shell, and finally the button battery was sealed with a press. Among the components of the button battery, the diaphragm is a polypropylene film (Celgard2300) and the electrolyte is a 1 mol / L LiPF6 solution.
[0072] The button battery obtained above was subjected to constant current charge and discharge test. At a voltage of 0.01-3 V, the battery was charged and discharged at 500 mA g -1 The first discharge capacity of the material can reach 1084.5 mAh g -1 After 900 cycles, the reversible discharge capacity remains at 940.4 mAh g -1 ; at 2000mA g -1 After 1400 cycles, the reversible discharge capacity remains at 551.6 mAh g -1 .
[0073] Comparative Example 1
[0074] The only difference between Comparative Example 1 and Example 5 is that phytic acid is not used as the phosphorus source, and phosphoric acid is used as the phosphorus source. Amorphous SnP2O7 cannot be obtained, and crystalline SnP2O7 is obtained. 7。 Because phytic acid itself can be used as an auxiliary carbon source to promote its amorphization, and further improve its conductivity and enhance its electrochemical performance. The crystalline SnP2O7 material obtained in Comparative Example 1 has a high conductivity at 500mA g -1 The first discharge capacity of the material can reach 1266.5 mAh g -1 After 900 cycles, the reversible discharge capacity is only 610.9 mAh g -1 ; at 2000mA g -1 After 600 cycles, the cycle stability was lost and the capacity slowly decreased. After that, the reversible discharge capacity increased from 505.4 mAh g -1Down to 407.1mAhg at 800 cycles -1 .
[0075] Comparative Example 2
[0076] The only difference between Comparative Example 2 and Example 5 is that the calcination temperature is 650°C. When the temperature exceeds 600°C, the higher temperature will increase the degree of reaction and consume the carbon in the sample to a certain extent, prompting the sample to crystallize, thereby synthesizing crystalline tin pyrophosphate. This sample has a calcination temperature of 500mA g -1 After 900 cycles, the reversible discharge capacity is only 596.2 mAh g -1 ; at 2000mAg -1 After 800 cycles, it began to collapse, and the reversible discharge capacity decreased from 520.1 mAh g -1 The capacity drops sharply to less than 400 mAh g at 1000 cycles. -1 .
[0077] Comparative Example 3
[0078] Comparative Example 3 is different from Example 5 in that citric acid monohydrate is not added to obtain crystalline SnP2O7. Citric acid is the main carbon source and a strong chelating agent. When the amount added is low, it is not easy for the raw materials to fully react, and the carbon content of the final sample is reduced, which reduces the conductivity of the material and the ability to inhibit volume expansion. At a voltage of 0.01 to 3V, at 500mAg -1 The first discharge capacity of the material can reach 1307 mAh g -1 After only 500 cycles, the reversible discharge capacity dropped to 502.5 mAh g -1 ; at 2000mA g -1 After 400 cycles, the reversible discharge capacity increased from 480.6 mAh g -1 It drops drastically until the battery collapses.
[0079] Comparative Example 4
[0080] The only difference between Comparative Example 4 and Example 5 is that 1.0 g of citric acid monohydrate was added. Although amorphous SnP2O7 was obtained, a large amount of carbon source introduced excessive carbon into the material, which reduced the overall cycle capacity of the material. -1 The first discharge capacity of the material can reach 994.8 mAh g -1 After 900 cycles, the reversible discharge capacity can only be maintained at 504.9 mAh g -1 ; at 2000mAg -1After 1400 cycles, the reversible discharge capacity can only be maintained at 373.6 mAh g -1 .
Claims
1. A method for preparing an amorphous lithium-ion battery negative electrode material, characterized in that: The steps include: (1) mixing a tin source, phytic acid and a carbon source in an inert atmosphere, and stirring them thoroughly to obtain a mixed solution; (2) freeze-drying the obtained mixed solution to obtain a precursor material; (3) calcining the precursor material under an inert atmosphere to obtain an amorphous lithium-ion battery negative electrode material.
2. The preparation method according to claim 1, characterized in that: In step (1), the tin source is at least one of tin tetrachloride pentahydrate, stannous chloride, tin sulfate or sodium stannate.
3. The preparation method according to claim 1, characterized in that: In step (1), the carbon source is at least one of citric acid monohydrate, oxalic acid or ascorbic acid.
4. The preparation method according to claim 1, characterized in that: In step (1), the phytic acid is a phytic acid solution with a volume fraction of 70 to 75%.
5. The preparation method according to claim 1, characterized in that: In step (1), the molar ratio of the tin source, phytic acid and carbon source added is 1:3-4:1-2.
6. The preparation method according to claim 1, characterized in that: In step (1), the stirring time is 0.5 to 2 hours, and the solution is stirred to such an extent that the volume of the solution is reduced to 45 to 50% of the initial volume.
7. The preparation method according to claim 1, characterized in that: In step (2), the freeze-drying parameters are stored at -35 to -30°C in a vacuum environment for 8 to 10 hours.
8. The preparation method according to claim 1, characterized in that: In step (3), the heating rate of calcination is 5-10°C / min, the calcination temperature is 400-600°C, the calcination time is 3-5h, and the cooling rate is 3-5°C / min.
9. The preparation method according to claim 1, characterized in that: In step (3), the inert atmosphere is nitrogen or argon.
10. The preparation method according to claim 1, characterized in that: In step (3), the amorphous lithium-ion battery negative electrode material is amorphous SnP2O7.
Citation Information
Cited By
Layered tin pyrophosphate composite negative electrode material and preparation method thereof
CN122035808A